Free Floating Thrombus in Carotid Artery in a Patient with Recurrent Strokes. (10th January 2017) - Roy, Moni; Roy, Ashish Kumar; DeSanto, Jeffrey R.; Abdelsalam, Murad
Abstract : We present a case of 72-year-old male with reported past medical history of recurrent transient ischemic attacks (TIAs) presenting with myriad of neurological symptoms. Patient was transferred from outlying hospital with complaints of right sided facial droop and dysarthria. Computed tomography angiography (CTA) showed high grade proximal left internal carotid artery (ICA) stenosis along with interesting finding of a free floating thrombus (FFT) in the left ICA. After discussion with the neurosurgical team, our case was treated conservatively with combination of antiplatelet therapy with Aspirin and anticoagulation with Warfarin without recurrence of TIAs or strokes on six-month follow-up.